Solid-state polymer electrolyte and preparation method and application thereof
Patent Information
- Application Number
- CN202310074638.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-12
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-01-12
AI Technical Summary
因此,现有技术中存在界面相容性差的问题
[0015]本发明实施例提供的固态聚合物电解质的制备方法,在混合溶液中添加锆钛酸铅,基于锆钛酸铅较高的介电常数,可以促进锂盐的解离和诱导锂离子均匀沉积,提升固态聚合物电解质的离子电导率的特性,并有效抑制锂枝晶生长,从而制备出高性能的固态聚合物电解质,该固态聚合物电解质具有较高的室温离子电导率和锂离子迁移数。而且,以本发明所制备的固态聚合物电解质为原料构成的锂金属电池具有较高的放电比容量以及良好的循环稳定性,前景发展广阔。
Smart Images

Figure CN116315119B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium metal battery technology, and more specifically, to a solid polymer electrolyte, its preparation method, and its application. Background Technology
[0002] Solid-state electrolytes are an ideal electrolyte material for addressing the safety issues of lithium metal batteries. Inorganic solid-state electrolytes, in particular, possess high intrinsic ionic conductivity and good mechanical properties, which can suppress lithium dendrite growth on the lithium anode side. However, they are difficult to match with the cathode, especially porous cathodes, resulting in extremely high interfacial impedance. In contrast, polymer solid-state electrolytes offer good flexibility and can form good interfacial contact with the cathode side. However, their low modulus makes it difficult to suppress lithium dendrite growth on the anode side, and the extremely low ionic conductivity of polymer solid-state electrolytes makes them unsuitable for practical applications.
[0003] To improve the ionic conductivity of polymer solid electrolytes, the most common method is to add inorganic fillers to the matrix, such as lithium-ion conductive fillers (lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium titanium aluminum phosphate) and inert fillers (silica, zinc dioxide, aluminum oxide). The former can construct additional ion transport channels, while the latter can reduce polymer crystallinity, ultimately increasing ionic conductivity. When constructing composite polymer solid electrolytes, most researchers focus on the uniform distribution of fillers. This ensures uniform ion transport channels and relatively uniform mechanical properties, thus limiting lithium dendrite growth to the greatest extent. However, a uniformly dispersed structure results in a high modulus on the positive electrode side, which makes the electrolyte incompatible with the porous positive electrode, reducing the interfacial compatibility on the positive electrode side. In fact, inducing uniform lithium-ion deposition through uniform lithium-ion transport channels does not require the filler to be uniformly distributed throughout the electrolyte in the direction perpendicular to the electrode; uniform distribution in the interfacial layer near the electrode, parallel to the electrode direction, is sufficient. However, the multilayer structure introduces a new organic-inorganic interface, which may negatively impact the overall interfacial compatibility of the battery. Therefore, existing technologies suffer from poor interfacial compatibility. In addition, there are challenges in constructing a laterally uniformly distributed interfacial layer of filler. If ion-conducting fillers are used, even if their distribution is uniform, their ion transport capacity differs significantly from that of the polymer itself, leading to uneven lithium-ion transport and the risk of dendrite growth. Simultaneously, in composite polymer solid-state electrolyte systems, ion dissociation and transport largely depend on the polymer itself, resulting in a limited number of free lithium ions. These ions are insufficient to deposit uniformly along the electrode and are instead attracted to lithium protrusions with higher potentials, accelerating their growth into lithium dendrites or even dead lithium. Therefore, improving the lithium salt dissociation capability of polymer solid-state electrolytes becomes another challenge. Summary of the Invention
[0004] In view of the above, the present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the present invention proposes a solid polymer electrolyte, its preparation method, and its application. The solid polymer electrolyte prepared by the polymer solid electrolyte and its method provided by the present invention has high ionic conductivity and lithium-ion transference number, and lithium-ion batteries prepared based on the solid polymer electrolyte of the present invention exhibit good battery cycle stability. Furthermore, the preparation method has a simple process flow and is suitable for large-scale industrial production applications.
[0005] Therefore, in a first aspect, embodiments of the present invention provide a method for preparing a solid polymer electrolyte, the method comprising: preparing a mixed solution: adding polyvinylidene fluoride and its copolymers, lithium salt and inert filler to a solvent, mixing and stirring evenly to obtain a mixed solution; preparing an electrolyte membrane: placing the mixed solution in a glass petri dish and evaporating it at high temperature to obtain the solid polymer electrolyte.
[0006] Preferably, the mass ratio of the polyvinylidene fluoride and its copolymer, the lithium salt and the inert filler is 2:[1-4]:[0.2-0.6].
[0007] Preferably, the polyvinylidene fluoride and its copolymers are one or more of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, and polyvinylidene fluoride-trifluoroethylene-trifluorochloroethylene.
[0008] Preferably, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide.
[0009] Preferably, the purity of the lithium salt is greater than 99.9%.
[0010] Preferably, the inert filler is lead zirconate titanate ceramic, which is granular with a particle size of 400-600 nanometers and a dielectric constant of 50-5000 at room temperature, normal pressure, and 10Hz.
[0011] Preferably, the solvent is one of N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran.
[0012] Preferably, the evaporation process includes blower drying and vacuum drying in sequence, wherein the temperature and time of blower drying are 45-65℃ and 18-22h, respectively, and the temperature and time of vacuum drying are 45-65℃ and 1-3h, respectively.
[0013] Secondly, embodiments of the present invention provide a solid polymer electrolyte material prepared by the method for preparing solid polymer electrolytes provided in the first aspect above.
[0014] Thirdly, embodiments of the present invention provide a lithium metal battery, comprising the solid polymer electrolyte material described in the second aspect above.
[0015] The method for preparing a solid polymer electrolyte provided in this invention involves adding lead zirconate titanate to a mixed solution. Based on the high dielectric constant of lead zirconate titanate, it can promote the dissociation of lithium salts and induce uniform lithium ion deposition, thereby improving the ionic conductivity of the solid polymer electrolyte and effectively suppressing lithium dendrite growth. This results in a high-performance solid polymer electrolyte with high room-temperature ionic conductivity and lithium-ion transference number. Furthermore, lithium metal batteries constructed using the solid polymer electrolyte prepared in this invention exhibit high discharge specific capacity and good cycle stability, showing promising development prospects. Attached Figure Description
[0016] Figure 1 This is a flowchart illustrating the preparation method of a solid polymer electrolyte provided in an embodiment of the present invention.
[0017] Figure 2 This is a schematic diagram of a method for preparing a solid polymer electrolyte according to an embodiment of the present invention.
[0018] Figure 3 The Li / Li symmetric cells provided in Embodiment 1 and Comparative Examples 1-2 of this invention were tested at 25°C and 0.1 mA / cm². 2 Cyclic performance at current density.
[0019] Figure 4 The LiNi provided in Embodiment 1 and Comparative Example 2 of the present invention 0.8 Co 0.1 Mn 0.1 Cyclic performance of O2(NCM811) / Li battery at 25℃ and 0.5C charge / discharge rate. Detailed Implementation
[0020] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0021] The following disclosure provides numerous different embodiments or examples for implementing various structures of the invention. To simplify the disclosure, specific examples of components and arrangements are described below. These are merely examples and are not intended to limit the invention. Furthermore, reference numerals and / or letters may be repeated in different examples. Such repetition is for simplification and clarity and does not in itself indicate a relationship between the various embodiments and / or arrangements discussed. Additionally, examples of various specific processes and materials are provided in this invention; however, those skilled in the art will recognize the applicability of other processes and / or the use of other materials.
[0022] This invention provides a solid polymer electrolyte, its preparation method, and its application, used to obtain a solid electrolyte with high ionic conductivity and lithium-ion transference number. Lithium metal batteries prepared based on the solid electrolyte of this invention exhibit good battery cycle performance and stability. Figure 1 and Figure 2 As shown, this method includes:
[0023] Step S1, Preparation of mixed solution: Polyvinylidene fluoride and its copolymers, lithium salt and inert filler are added to solvent, mixed and stirred evenly to obtain mixed solution.
[0024] The mass ratio of the polyvinylidene fluoride and its copolymer, the lithium salt and the inert filler is 2:[1-4]:[0.2-0.6].
[0025] The polyvinylidene fluoride and its copolymers may be one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-trifluoroethylene (P(VDF-TrFE)), and polyvinylidene fluoride-trifluoroethylene-trifluorochloroethylene (P(VDF-TrFE-CTFE)). The lithium salt may be one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI). The purity of the lithium salt is greater than 99.9%.
[0026] Furthermore, the inert filler is lead zirconate titanate ceramic, in granular form, with a particle size of 400-600 nanometers and a dielectric constant between 50-5000 at room temperature, normal pressure, and 10Hz. The solvent is one of N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran. The stirring time is 10 hours.
[0027] Step S2, Preparation of electrolyte membrane: The mixed solution obtained in step S1 is placed in a glass petri dish and evaporated at high temperature to obtain the solid polymer electrolyte.
[0028] The evaporation process includes blower drying and vacuum drying, wherein the temperature and time for blower drying are 45-65℃ and 18-22h, respectively, and the temperature and time for vacuum drying are 45-65℃ and 1-3h, respectively.
[0029] The blower drying is used to remove excess solvent from the mixed solution, and the vacuum drying is used to remove moisture from the mixed solution to avoid the final solid polymer electrolyte containing water.
[0030] The solid polymer electrolyte and its preparation method provided in this invention promote lithium salt dissociation and induce uniform lithium ion deposition by adding lead zirconate titanate during the preparation process, thereby improving the ionic conductivity of the solid polymer electrolyte and effectively suppressing lithium dendrite growth. Secondly, in an electric field, zirconium atoms and titanium atoms in lead zirconate titanate shift to form dipoles. These dipoles can construct unique dipole channels, inducing uniform lithium ion transport along the channels, thus suppressing lithium dendrite growth. Furthermore, the gradient structure of the polyvinylidene fluoride electrolyte with added lead zirconate titanate allows the side with a high lead zirconate titanate content to have a high modulus, enabling it to adhere to the lithium anode and further suppressing lithium dendrites. The other side contains less lead zirconate titanate, maximizing the retention of the flexibility of the polyvinylidene fluoride polymer solid electrolyte and ensuring good interfacial compatibility with the cathode. Since the generation of this gradient structure relies on the deposition of lead zirconate titanate in a low-viscosity solution, this method does not introduce additional interfaces as in conventional multilayer structures. The combined effect of the above factors results in a significantly improved ionic conductivity, lower interfacial impedance, and better lithium dendrite suppression capability of the polymer solid electrolyte. The cycle performance of lithium metal batteries prepared based on this solid polymer electrolyte is also greatly improved.
[0031] Furthermore, the method for preparing the solid polymer electrolyte provided by this invention rationally utilizes the mass ratio of polyvinylidene fluoride (PVDF) to lithium salt, maintaining a high level of ionic conductivity. In addition, the rational use of the mass ratio of PVDF and its copolymers to inert fillers ensures a high dielectric constant for the electrolyte. Simultaneously, this preparation method has a simple process flow and is suitable for large-scale industrial production.
[0032] The following detailed description, in conjunction with some specific embodiments, further illustrates the specific process and effects of the preparation method of the solid polymer electrolyte of the present invention, but does not limit the scope of protection of the present invention.
[0033] Unless otherwise specified, all chemical reagents and materials used in this invention were purchased through commercial channels.
[0034] Example 1
[0035] This embodiment provides a method for preparing a solid polymer electrolyte, including the following steps:
[0036] Preparation of the mixed solution: Polyvinylidene fluoride, lithium bis(trifluoromethanesulfonyl)imide and lead zirconate titanate were mixed in a mass ratio of 1:1:0.2 and added to N,N-dimethylformamide solvent. The mixture was stirred at room temperature for 10 hours to form a homogeneous mixed solution.
[0037] Preparation of electrolyte membrane: The well-mixed solution was poured into a glass petri dish and placed in a forced-air oven at 55°C for 19 hours, and then placed in a vacuum oven at 55°C for 1 hour. The formed membrane was then peeled off from the glass petri dish to obtain a solid polymer electrolyte.
[0038] Example 2
[0039] This embodiment provides a method for preparing a solid polymer electrolyte, including the following steps:
[0040] Preparation of the mixed solution: Polyvinylidene fluoride, lithium difluorosulfonylimide and lead zirconate titanate were mixed in a mass ratio of 1:1:0.2 and added to N,N-dimethylformamide solvent. The mixture was stirred at room temperature for 10 hours to form a homogeneous mixed solution.
[0041] Preparation of electrolyte membrane: The well-mixed solution was poured into a glass petri dish and placed in a forced-air oven at 55°C for 19 hours, and then placed in a vacuum oven at 55°C for 1 hour. The formed membrane was then peeled off from the glass petri dish to obtain a solid polymer electrolyte.
[0042] The difference between Example 2 and Example 1 is that the lithium salt used in this example is lithium bis(fluorosulfonyl)imide.
[0043] Example 3
[0044] This embodiment provides a method for preparing a solid polymer electrolyte, including the following steps:
[0045] Preparation of the mixed solution: Polyvinylidene fluoride-trifluoroethylene, lithium bis(trifluoromethanesulfonyl)imide and lead zirconate titanate were mixed in a mass ratio of 1:1:0.2 and added to N,N-dimethylformamide solvent. The mixture was stirred at room temperature for 10 hours to form a homogeneous mixed solution.
[0046] Preparation of electrolyte membrane: The well-mixed solution was poured into a glass petri dish and placed in a forced-air oven at 55°C for 19 hours, and then placed in a vacuum oven at 55°C for 1 hour. The formed membrane was then peeled off from the glass petri dish to obtain a solid polymer electrolyte.
[0047] The difference between Example 3 and Example 1 is that the polyvinylidene fluoride and its copolymer used in this example are polyvinylidene fluoride-trifluoroethylene.
[0048] Comparative Example 1
[0049] This embodiment provides a method for preparing a solid polymer electrolyte, including the following steps:
[0050] Preparation of the mixed solution: Polyvinylidene fluoride, lithium bis(trifluoromethanesulfonyl)imide and aluminum oxide were mixed in a mass ratio of 1:1:0.2 and added to N,N-dimethylformamide solvent. The mixture was stirred at room temperature for 10 hours to form a homogeneous mixed solution.
[0051] Preparation of electrolyte membrane: The well-mixed solution was poured into a glass petri dish and placed in a forced-air oven at 55°C for 19 hours, and then placed in a vacuum oven at 55°C for 1 hour. The formed membrane was then peeled off from the glass petri dish to obtain a solid polymer electrolyte.
[0052] The difference between Comparative Example 1 and Example 1 is that the inert filler used in this comparative example is aluminum oxide.
[0053] Comparative Example 2
[0054] This embodiment provides a method for preparing a solid polymer electrolyte, including the following steps:
[0055] Preparation of the mixed solution: Polyvinylidene fluoride and lithium bis(trifluoromethanesulfonyl)imide were mixed in a mass ratio of 1:1 and added to N,N-dimethylformamide solvent. The mixture was stirred at room temperature for 10 hours to form a homogeneous mixed solution.
[0056] Preparation of electrolyte membrane: The well-mixed solution was poured into a glass petri dish and placed in a forced-air oven at 55°C for 19 hours, and then placed in a vacuum oven at 55°C for 1 hour. The formed membrane was then peeled off from the glass petri dish to obtain a solid polymer electrolyte.
[0057] The difference between Comparative Example 2 and Example 1 is that no inert filler was added in this comparative example.
[0058] The solid polymer electrolytes prepared in Examples 1-3 and Comparative Examples 1-2 were tested for ionic conductivity, activation energy, lithium-ion transference number, and battery cycle performance. The specific test methods are as follows:
[0059] (1) Ionic conductivity test: The solid polymer electrolyte is assembled into a steel sheet-solid electrolyte-steel sheet (SS / SSEs / SS) battery in a glove box filled with argon gas. The AC impedance is tested using an electrochemical workstation, and the ionic conductivity is calculated using the following formula 1.
[0060]
[0061] Where L is the thickness of the electrolyte membrane, R is the EIS impedance of the SS / SSEs / SS battery, and S is the area of the steel sheet.
[0062] (2) Activation energy calculation: After obtaining the ionic conductivity at different temperatures, the data is plotted and fitted, and the activation energy of lithium ion migration is calculated by combining it with Formula 2.
[0063]
[0064] Where σ0 is the pre-exponential factor, E a It is the activation energy.
[0065] (3) Ion transport number calculation: After assembling the electrolyte into a lithium metal-solid electrolyte-lithium metal (Li / SSEs / Li) battery, EIS testing was performed at room temperature with a frequency of 7MHz to 1Hz and an amplitude of 10mV. The impedance R0 was recorded at this time. Then, a polarization voltage of 10mV was continuously applied, and the initial response current I0 was recorded. When the steady-state current (I0) was reached... s After that, stop applying voltage and perform the EIS test again, recording the impedance R at this point. s The calculation formula is shown in Figure 3:
[0066]
[0067] Where I0 is the initial response current, R0 is the initial impedance, and I s For steady-state current, R s The impedance at which steady-state current is achieved.
[0068] (4) Battery cycle performance test: The above electrolytes were assembled into NCM811 / lithium metal full cells and tested at 25°C and 0.5C rate.
[0069] The test results for the product performance in Examples 1-3 and Comparative Examples 1-2 are shown in Table 1.
[0070] Table 1, Examples and comparative examples Test items and test results
[0071]
[0072] Based on the above embodiments and comparative examples, and by comparing the test results obtained from testing them, the following conclusions can be drawn:
[0073] (1) Under the same preparation conditions, compared with Comparative Examples 1-2, the solid polymer electrolytes prepared in Examples 1-3 have higher ionic conductivity, lower activation energy, and better battery cycle performance because they use lead zirconate titanate with a high dielectric constant as an inert filler. This indicates that lead zirconate titanate with a high dielectric constant not only increases the mechanical strength of the electrolyte, but also promotes the efficient dissociation of lithium salts and forms continuous dipole channels at the interface, inducing continuous, uniform, and efficient transport of lithium ions along the electrode, thereby significantly improving the ionic conductivity of the solid polymer electrolyte and improving the battery cycle stability.
[0074] (2) Under the same preparation conditions, the ionic conductivity of the solid polymer electrolyte prepared in Example 2 was slightly improved compared to Example 1. This is because lithium trifluoromethanesulfonylimide provides fewer anionic groups, resulting in a weaker attraction for lithium ions and thus a stronger dissociation ability of the lithium salt.
[0075] (3) Under the same preparation conditions, compared with Examples 1-2, the solid polymer electrolyte prepared in Example 3 showed a significant increase in ionic conductivity and a significant increase in transport number. This is because, with the addition of trifluoroethylene monomer, the material always exhibits a strongly polar TTTT conformation, with all molecular chain dipoles aligned in the same direction, resulting in a strong polarity and thus a significant improvement in the dissociation ability of lithium salt.
[0076] To further test the ability of the solid polymer electrolyte provided in this invention to suppress lithium dendrite growth, the solid polymer electrolytes prepared in Example 1 and Comparative Examples 1-2 were assembled into lithium-lithium symmetric batteries for testing. The experimental results are as follows: Figure 3 As shown, the lithium-lithium symmetric battery assembled using the solid polymer electrolyte in Example 1 operates at a current density of 0.1 mA / cm² at room temperature. 2 The battery achieved stable cycling for 1900 hours. Under the same test conditions, the lithium-lithium battery assembled using the solid polymer electrolyte in Comparative Example 1 short-circuited after only 200 hours of cycling, and the lithium-lithium battery assembled using the solid polymer electrolyte in Comparative Example 2 short-circuited after only 140 hours of cycling. This indicates that the solid polymer electrolyte prepared by the method provided in this invention has excellent ability to suppress lithium dendrite formation because its system contains more free lithium ions and provides more uniform lithium ion transport channels, offering more opportunities for uniform deposition of lithium ions on the lithium anode.
[0077] To illustrate the compatibility between the solid polymer electrolyte provided in this invention and the high-voltage NCM811 cathode, the solid polymer electrolytes prepared in Example 1 and Comparative Example 2 were assembled into NCM811-lithium full cells for long-cycle performance testing. The experimental results are as follows: Figure 4As shown, the NCM811-lithium full cell assembled using the solid polymer electrolyte in Example 1 retains 86.2% capacity after 500 cycles at room temperature and 0.5C rate, and 99.8% capacity after 140 cycles. In contrast, under the same test conditions, the NCM811-lithium full cell assembled using the solid polymer electrolyte in Comparative Example 2 only retains 75.6% capacity after 140 cycles. This indicates that the solid polymer electrolyte prepared by the method provided in this invention can be better matched with a high-voltage cathode, which is helpful for preparing high-energy-density lithium metal batteries.
[0078] In summary, the solid polymer electrolyte, its preparation method, and its applications provided by the embodiments of this invention involve adding lead zirconate titanate to a mixed solution. Based on the high dielectric constant of lead zirconate titanate, this promotes the dissociation of lithium salts and induces uniform lithium ion deposition, thereby enhancing the ionic conductivity of the solid polymer electrolyte and effectively suppressing lithium dendrite growth. This results in a high-performance solid polymer electrolyte with high room-temperature ionic conductivity and lithium-ion transference number. Furthermore, lithium metal batteries constructed using the solid polymer electrolyte prepared by this invention exhibit high discharge specific capacity and good cycle stability, showing promising development prospects.
[0079] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0080] Although embodiments of the invention have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the claims and their equivalents.
Claims
1. A method for preparing a lithium metal battery, characterized in that, Including solid polymer electrolytes, the preparation method includes: Preparation of mixed solution: Polyvinylidene fluoride and its copolymers, lithium salt and inert filler are added to solvent, mixed and stirred evenly to obtain mixed solution; Preparation of electrolyte membrane: The mixed solution was placed in a glass petri dish and evaporated at high temperature to obtain the solid polymer electrolyte; The mass ratio of the polyvinylidene fluoride and its copolymers, the lithium salt, and the inert filler is 2:[1-4]:[0.2-0.6]. The polyvinylidene fluoride and its copolymers are one or more of polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, and polyvinylidene fluoride-trifluoroethylene-trifluorochloroethylene. The lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide and lithium bis(fluorosulfonyl)imide; The purity of the lithium salt is greater than 99.9%; The inert filler is lead zirconate titanate ceramic, which is granular with a particle size of 400-600 nanometers and a dielectric constant of 50-5000 at room temperature, normal pressure and 10Hz. The solvent is one of N,N-dimethylformamide, N-methylpyrrolidone, and tetrahydrofuran; The solid polymer electrolyte has a gradient structure. The side with a high lead zirconate titanate content has a high modulus and fits well with the lithium anode, while the other side with less lead zirconate titanate has good interfacial compatibility with the cathode. This gradient structure is formed by the deposition of lead zirconate titanate in a low viscosity solution.
2. The preparation method according to claim 1, characterized in that, The evaporation process includes blower drying and vacuum drying, wherein the temperature and time for blower drying are 45-65℃ and 18-22h, respectively, and the temperature and time for vacuum drying are 45-65℃ and 1-3h, respectively.
3. A lithium metal battery, characterized in that, The lithium metal battery uses a preparation method comprising any one of claims 1-2.
4. The lithium metal battery according to claim 3, characterized in that, The lithium metal battery includes a solid polymer electrolyte.
Citation Information
Patent Citations
Asymmetric solid electrolyte, preparation method thereof and application thereof in high-voltage solid-state battery
CN111276738A
Preparation method of polymer-based solid electrolyte membrane and battery
CN114335709A
Solid polymer electrolyte and preparation method and application thereof
CN114678589A
Composite electrolyte with stable gradient distribution structure, battery and preparation method
CN115441048A
Solid Electrolyte Membrane And All-Solid-State Battery Comprising Same
US20210288354A1